Comparative pharmacodynamics of intranasal and enteral administration of captopril for uncomplicated hypertensive crises - I. L. Kechyn; V. V. Hladyshev; I. О. Pukhalska (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2021)
Uncomplicated hypertensive crises without acute or progressive damage to the target organs pose a potential threat to the patient’s life and require rapid reduction of arterial pressure within hours or days in an outpatient setting. The existing protocol for the treatment of this pathology is not entirely perfect, as it does not offer the primary physician a clear and unambiguous description of the use of effective and complementary drugs. The use in these cases of nasal transport of antihypertensive active pharmaceutical ingredients in appropriate dosage forms makes it possible to ensure their rapid delivery to the bloodstream and perivascular structures of the brain.